A biomechanical study after combined reconstruction of the anterior cruciate and anterolateral ligaments: Comparison between anatomic anterolateral ligament reconstruction and lateral tenodesis using the modified Lemaire technique. Issue 2 (28th February 2020) - Delaloye, Jean-Romain; Hartog, christoph; Blatter, Samuel; Müller, Dominik; Schläppi, Michel; Denzler, Dario; Murar, Jozef; Koch, Peter
Objectives: To determine the stabilizing role of the anterolateral ligament reconstruction (ALLR) and the modified Lemaire lateral extraarticular tenodesis (LET) performed in combination with anterior cruciate ligament reconstruction (ACLR) and to determine if one of these two procedures was superior to the other. Methods: Six non paired cadaveric knees were tested with a 6 degrees of freedom robotic system (KUKA Robotics). Internal rotation and anterior tibial translation were measured between 0 and 90° knee flexion after applying 5 N-m Torque and a 134-N anterior load, respectively. A full kinematics assessment was performed in each following conditions: intact knee, after section of the anterior cruciate ligament (ACL), after section of the ACL and anterolateral ligament (ALL) and Kaplan fibers, after isolated ACLR, after combined ACLR+LET and ACLR+ALLR. ALLR was performed using Gracilis tendon while central strip of the ilio-tibial band was used for the modified Lemaire procedure. These different states were compared using a Tukey paired comparison test. Results: In combined ACL and anterolateral deficient knee, anterior translation and internal rotation remained significantly increased after isolated ACLR compared to intact knee (+2.33 ± 1.44 mm and +1.98 ± 1.06°; p > 0.01). On the other hand, the addition of an ALLR or a modified Lemaire LET to the ACLR allowed to restore anterior translation and internal rotation to values similar to the intact knee. Finally, the two anterolateral procedures had not significantly different values in both tests. This difference was 0.67 ± 1.46 mm for anterior translation (p=0.79) and 0.11 ± 1.11° for internal rotation (p=0.99). Conclusion: In ACL and anterolateral deficient knee, combined ACLR and anterolateral reconstruction allowed restoration of native stability of the knee in anterior translation and internal rotation contrary to isolated ACLR. Additionally, both types of extra-articular reconstruction, ALLR or modified Lemaire procedure, were similar in terms of restoring knee kinematics and neither overconstrained the knee.